2007
DOI: 10.1212/01.wnl.0000256348.65744.b2
|View full text |Cite
|
Sign up to set email alerts
|

MR tractography depicting damage to the arcuate fasciculus in a patient with conduction aphasia

Abstract: An 84-year-old right-handed man with a history of atrial fibrillation and a left parietal lobe infarct was admitted to the stroke unit due to a sudden decline in responsiveness. He was awake but silent, though his comprehension was intact. Slight weakness was noted in his right upper and lower extremities. On the third day, the patient regained his voice, but his speech was impaired with paraphasic errors and naming difficulties. Repetition was markedly impaired. The clinical findings suggested motor/conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…More recent studies have shown that it may also be used to measure patient outcomes after stroke. [39][40][41] Attempts have also been made to assess the language circuits, [42][43][44] including the arcuate fasciculus, aˆber tract that connects the temporal lobe (primary auditory cortex), Wernicke's area, and Broca's area (frontal lobe). Thisˆber bundle is considered to be eloquent when the left hemisphere is considered, and vascular insult to this circuit can result in conduction aphasia.…”
Section: Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have shown that it may also be used to measure patient outcomes after stroke. [39][40][41] Attempts have also been made to assess the language circuits, [42][43][44] including the arcuate fasciculus, aˆber tract that connects the temporal lobe (primary auditory cortex), Wernicke's area, and Broca's area (frontal lobe). Thisˆber bundle is considered to be eloquent when the left hemisphere is considered, and vascular insult to this circuit can result in conduction aphasia.…”
Section: Ischemic Strokementioning
confidence: 99%
“…Thisˆber bundle is considered to be eloquent when the left hemisphere is considered, and vascular insult to this circuit can result in conduction aphasia. 43 Studies have shown that the degree of damage to this circuit can predict the patient's language function in the chronic stage following the vascular event. 44 Tractography has also been used in theˆeld of pediatric ischemic brain insult.…”
Section: Ischemic Strokementioning
confidence: 99%
“…According to Geschwind [18], disconnection syndromes were higher function deficits that resulted from white matter lesions or lesions of the association cortices; conduction aphasia was usually presented as the prototypal example of a disconnection syndrome. Since then, it has been generally assumed that, in conduction aphasia, the lesion affects the arcuate fasciculus [19,20] and sporadically an indirect pathway passing through the inferior parietal cortex [21••].…”
Section: Conduction Aphasia As a Disconnection Syndromementioning
confidence: 99%
“…It is not easy to find cases of conduction aphasia with a lesion limited to the arcuate fasciculus. Although the arcuate fasciculus is often reported to be involved in conduction aphasia [19,20,28], cortical lesions alone without subcortical extension may also produce conduction aphasia [29,30]; furthermore, patients with lesions of the arcuate fasciculus may retain the language repetition ability [31,32], suggesting that the arcuate fasciculus is not crucial for language repetition.…”
Section: Neuroimaging Studies Of Conduction Aphasiamentioning
confidence: 99%
“…42 Cognitive studies as yet are limited but an elegant report by Yamada et al clearly shows quantifiable damage to the arcuate fasciculus in conduction aphasia. 43 A number of disconnection syndromes have also been studied in this way with correlation between the neuropsychological deficit and affected tracts. 41 Other data relating cognitive changes to tractography are so far few, but this technique promises expansion in hodology with the ultimate promise of standardized 3D hodological atlases.…”
Section: Neuroimaging Tractographymentioning
confidence: 99%